The army’s participation in maintaining the public order in the Kingdom of Hungary between 1867–1918 - Attila Vedó (Belügyi Szemle, 2022)
Aim: As forces originally designed to protect the country against attacks from the outside are required in maintaining the public order amidst extraordinary circumstances today, it was no different in the civic Hungarian state born with the Compromise. The aim of this study is to present a specific segment of the internal policing structure before 1918, the tasks of the armed forces. Methodology: document and content analysis. Findings: The dualist setup of the Austro-Hungarian Empire and the relationship within the Hungarian Kingdom’s public order defense organisations and to the civil administration created a unique environment which military units ordered to support police organs of insufficient staffing or capacity had to comply with. In the examined time period, the army’s participation in the joint fighting service of the Austro-Hungarian Empire’s and the Royal Hungarian Army’s engagement in maintaining the public order was common practice, since until the 1885 establishment of the Royal Hungarian Gendarmerie, there was no military organised armed guard force bearing sufficient staffing, equipment and authorization, except in certain towns. As per its military organisational structure, the gendarmerie worked together with the defense forces in an effective way, and has practically taken over the majority of tasks from the armed forces. The current study examines how the armed forces’ activities by the military fit into the Hungarian public administration and what was the relationship like between the administrative authority ordering and the tactical combat force being ordered. Examining the armed forces’ tasks in the era is therefore necessary, both in its narrow and wider context, and paying special attention to the unique position of the Royal Hungarian Gendarmerie is also important, which could both be in the position to order the force of arms unites and be ordered. Value: Due to space constraints, the present study does not allow for detailed presentation of the wider range of armed force tasks and their background laid down in the law and various rules, it rather focuses on systematically reviewing the topic and painting a general picture. The topic is still relevant today in the context of the contribution of the armed forces to law enforcement. The historical context explored in this study may also help to inform the development of regulation in the present.